Hemostáza analogy vazopresinu pri konizacích cípku a pri malých vaginálních operacích - Jelínek, J; Huvar, I; Roztocil, A; Pilka, L (Ceska gynekologie, 1997)
Peroperative haemorrhage is a frequent complication of conization of the portio uteri by surgery-by a "cold knife" scalpel or another method (LEEP, laser, etc.). In a clinical study comprising 41 patients with the diagnosis CIN I-III or laceration of the portio uteri classical conization by means of a scalpel was made with concurrent haemostasis with terlipressin (TLP) by paracervical administration (400 micrograms-REMESTYP 2 amp.). Concurrently the blood loss in ml was followed, the Hb level and other effects of the preparation. From the results ensues that side-effects after local administration of TLP were observed only in 12.2%. Peroperative blood losses were on average under 15 ml. Local paracervical TLP administration appears effective from the clinical aspect with regard to the low frequency of side-effects and the favourable haemostatic effect.
Keywords: krvácení při operaci; Female; Lypressin; ženské pohlaví; Vagina; cervix uteri; lypresin; Blood Loss, Surgical; lidé; nádory děložního čípku; Hemostasis, Surgical; konizace děložního čípku; Conization; Terlipressin; Uterine Cervical Neoplasms; Uterine Cervical Dysplasia; terlipresin; Cervix Uteri; hemostáza chirurgická; vagina; dysplazie děložního hrdla; Humans